Analysis of Social Support with Exclusive Breastfeeding at the South Balantak Health Center, Banggai Regency - Intan Fazrin; Eta Rano (Journal of Health Science Community, 2022)
According to Riskesdas in 2018, the coverage of exclusive breastfeeding in Indonesia was 74.5%. Data from the Banggai district shows that the coverage of exclusive breastfeeding in 2019 was 65.2%. While in the area of ​​the southern Balantak health center it was 59.6%. The data indicate that there are still many babies who are not given exclusive breastfeeding. Social support is an external factor that affects exclusive breastfeeding for infants. The purpose of this study is to analyze the relationship between social support and exclusive breastfeeding at the South Balantak Health Center, Banggai Regency .This study uses a cross sectional design, sampling using accidental sampling technique. The number of samples is 34 respondents. The variables analyzed were social support and exclusive breastfeeding. While the data analysis using the chi-square test. The results showed that most of the respondents had social support in the less category as much as 52.9%. Most of the toddlers were not given exclusive breastfeeding as much as 64.7%. Analysis of the relationship between Social support and exclusive breastfeeding obtained a p-value of 0.003 < 0.05. The conclusion is that there is a relationship between Social support and exclusive breastfeeding at the South Balantak Health Center, Banggai Regency. Efforts to overcome the problem of exclusive breastfeeding are one of them by providing counseling to mothers of toddlers.